The Effect of Handgrip and Catch-Only Training on The Accuracy of The Backhand Drive in Table Tennis - Dewi Puspitasari; Aziz Amrulloh (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
The results of the observations indicate that training programs still tend to be monotonous, with a greater focus on repeating basic techniques without incorporating more varied methods. This results in athletes’ accuracy skills not developing optimally. This study aims to determine the effect of handgrip and catch-only training on the accuracy of the table tennis backhand drive, as well as to compare the effectiveness of the two methods. This study employs a quantitative approach and experimental methods, utilizing a quasi-experimental two-group pre-test-post-test design. The sample consisted of 12 athletes selected using total sampling. The instrument used in this study was the backhand drive accuracy test according to Tomoliyus. Data analysis techniques included the Paired Sample T-Test and linear regression analysis using the Model Summary. In the handgrip training group, the average accuracy score at the pre-test was 61.33 points, and the average post-test score was 66.33 points. In the catch-only training group, the average accuracy score at the pre-test was 57.83 points, and the average post-test score was 77.33 points. The p-value (Sig. 2-tailed) for the handgrip training group was 0.376 (value > 0.05), and the p-value (Sig. 2-tailed) for the catch-only training group was 0.025 (value < 0.05). The percentage effects of the handgrip and catch-only training methods were 57% and 80.2%, respectively. The conclusion of this study is that both training methods in this study had an effect on the accuracy of the athletes’ backhand drive strokes; however, there was a significant effect on backhand drive accuracy before and after the catch-only training compared to the handgrip training. A limitation of this study is that research specifically examining the relationship between grip strength training and reaction speed in relation to backhand drive accuracy remains limited.